2019
DOI: 10.11648/j.abb.20190703.12
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence of Nurses in Tertiary Hospitals in Dali, the People’s Republic of China

Abstract: Emotional intelligence plays an important role in regulating the emotions induced by fatigue or stress and it is critically required in nurses who work in dynamic hospital environments. Nurses' emotional intelligence helps them to create a positive work environment in various unfavorable situations in order to provide patients care in a supportive manner. The aim of this study was to assess nurses' emotional intelligence in tertiary hospitals in Dali, the People's Republic of China. The participants were 291 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
(16 reference statements)
3
7
0
Order By: Relevance
“…The majority of the nurses were female (84.6%), and the minority were male (15.4%). This is similar to the study conducted by Hua et al (2019), where their studies comprised of 99.31% female nurses and 0.69% male nurses. In this study, there were more nurses whose age was <28 years (50.8%), compared to those ≥ 28 years (49.2).…”
Section: Demographic Datasupporting
confidence: 87%
See 4 more Smart Citations
“…The majority of the nurses were female (84.6%), and the minority were male (15.4%). This is similar to the study conducted by Hua et al (2019), where their studies comprised of 99.31% female nurses and 0.69% male nurses. In this study, there were more nurses whose age was <28 years (50.8%), compared to those ≥ 28 years (49.2).…”
Section: Demographic Datasupporting
confidence: 87%
“…In this study, there were more nurses whose age was <28 years (50.8%), compared to those ≥ 28 years (49.2). However, another study showed that there were 57.73% of nurses whose age ranged from 20-30 years, 31.62% of those whose age ranged from 31-40 years, and only 10.65% of nurses with age ranging from 41-50 years and above (Hua et al, 2019). This also indicated that both our study and other study were similar, where the number of respondents comprised of younger nurses compared to the older nurses.…”
Section: Demographic Datasupporting
confidence: 75%
See 3 more Smart Citations